PENGARUH MEDIA MIND MAPPING TERHADAP PENGETAHUAN IBU RUMAH TANGGA DALAM PENCEGAHAN PENYAKIT DIARE DI DAERAH RAWAN BANJIR DI KECAMATAN MATANGKULI KABUPATEN ACEH UTARA - Rosdiana .; Khairuddin .; Imran . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Flood is a natural disaster that needs attention, because it threatens people's lives and economy. Various kinds of environmental damage caused by floods include the destruction of residential areas, the difficulty of getting clean water, damaged facilities and infrastructure, the destruction of agricultural areas, and the emergence of disease outbreaks one of them is diarrhea. The purpose of this study is to determine the effect of mind mapping media on the knowledge of housewives in the prevention of diarrheal diseases in flood-prone areas in the District of Matangkuli, North Aceh Regency. The research design is using quantitative approach. This research has been done in Gampong Tanju Ali in Matangkuli Sub-district, North Aceh District, the research was conducted on 11 s / d 19 (Post Test) and 21 s / d 25 (Pre Test) July 2017, in this research is housewife as flood victim living in flood prone area at Gampong Tanjong Tengku Ali in District of Matangkuli Regency of North Aceh. The result of this research shows that there is influence of mind mapping media between knowledge of housewife and prevention of diarrhea disease in flood prone area in Kecamatan Matangkuli of North Aceh Regency